THE INFLUENCE OF PBL MODEL AND CRITICAL THINKING SKILLS ON MATHEMATICS LEARNING OUTCOMES OF GRADE V ELEMENTARY SCHOOL STUDENTS IN KELEKAR DISTRICT, MUARA ENIM REGENCY - Susilawati susilawati; khoirawati; Suroyo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of PBL model and critical thinking skills on mathematics learning outcomes. This research is a quantitative research with a quasi-experimental method. The population in this study is grade V elementary school students in Kelekar district, while the sample was taken using the Cluster random sampling technique, the number of samples taken was 40 consisting of the Experimental class (class V SDN 3 Kelekar) and the Control class (class V SDN 1 Kelekar). Data was obtained using learning outcome instruments and critical thinking skills instruments. The data analysis technique used a separate test of independent sample T and Anova 2 paths. The results of the study with the independent sample T differential test showed that the significance value (2-tailed) was 0.003 meaning it was smaller than 0.05, and t count was 3.200 greater than the t table which was 2.715 which means that there was a difference in the average learning outcomes of students who studied using the PBL model and students who studied using the conventional model, the results of the two-path anova test showed that significance value = 0.015 < 0.05 means that there is an interaction between the PBL model and critical thinking skills on mathematics learning outcomes together. This study proves that there is an influence of the PBL model and critical thinking skills on the mathematics learning outcomes of grade V elementary school students in Kelekar district.